Monitoring electroactive ions at manganese dioxide pseudocapacitive electrodes with scanning electrochemical microscope for supercapacitor electrodes - Wittstock, Gunther (2013)
Hierarchical nanostructures of hydrated α-manganese dioxide (MnO2) are prepared and their kinetics properties are characterized using scanning electrochemical microscopy (SECM). The SECM measurements are focused on the feedback mode approach curve to extract the effective heterogeneous charge transfer rate constant and illustration of the ultramicroelectrode (UME) tip-substrate cyclic voltammetry. Positive feedback current is observed during the SECM approach curve, indicating the efficient charge transfer process into the MnO2 electrode. These studies complement electrochemical impedance spectroscopy and charge discharge measurements that are carried out to determine the effectiveness of the resultant MnO2 for supercapacitor application. Specific capacitance as high as 356 F g−1 at 2 A g−1 is achieved and there is no degradation of the capacitance after 2000 cycles of cycling test, indicating its good capacitive properties for supercapacitor application.